Descriptions of four new sponge-inhabiting barnacles (Thoracica: Archaeobalanidae: Acastinae) - Yu, Meng-Chen; Kolbasov, Gregory A.; Hosie, Andrew M.; Lee, Tse-Min; Chan, Benny K.k. (Zootaxa, 2017)
Within the family Archaeobalanidae, the sponge-inhabiting barnacles include species from the subfamilies Acastinae and Bryozobiinae as well as from the genus Membranobalanus in the subfamily Archaeobalaninae. Members of these groups are obligatory symbionts of poriferans, but the Acastinae can also be found in association with alcyonaceans and antipatharians. Acasta sulcata Lamarck, 1818, is one of the most widely reported sponge-inhabiting barnacle species, with numerous records across the Indo-West Pacific region revealing significant morphological variation. A combined morphological and molecular approach has revealed high diversity in recent collections of sponge-inhabiting barnacles in Taiwan and Australia, and four new species, namely Acasta aspera sp. nov., Acasta huangi sp. nov., Acasta radenta sp. nov., and Acasta undulaterga sp. nov., have been described here. All four species are morphologically close to A. sulcata, and the morphological similarity between these proposed species has led to the proposal of a “sulcata species complex.”